Analysis of FKIP Students' Perception Towards The Implementation of The PjBL Model In Improving Creativity and Learning Independence - Wahidah, Nina Ikhwati; Iskandar, Iskandar; Pixyoriza, Pixyoriza (Lembaga Penelitian dan Pendidikan Mandala, 2025)
In the era of 21st century education, a learning approach that can encourage creativity and learning independence is needed to prepare students to face global challenges. One of the learning models that is considered effective in this context is Project Based Learning (PjBL). This study aims to analyze the perceptions of FKIP students towards the implementation of the PjBL model and its impact on increasing creativity and learning independence. The method used in this study is a quantitative survey method with a descriptive and correlational approach. A sample of 100 students was selected by simple random sampling. The results showed that the majority of students had a positive perception of the implementation of PjBL (76% in the